Mirror-enhanced acceleration-induced geometric phase - Dipankar Barman; Debasish Ghosh; Bibhas Ranjan Majhi (European Physical Journal C: Particles and Fields)
Abstract Fulling–Davies–Unruh effect contains great amount of theoretical importance in various branches of physics. Requirement of very high acceleration hinders its experimental evidence. We put forward an idea to experimentally probe this effect by utilizing the Pancharatnam–Berry phase of an accelerated atom in presence of mirrors. We show that for much lower accelerations, the phase gets significantly enhanced in the presence of mirrors. We propose a schematic design of an interferometric set-up to experimentally capture this effect by utilizing the phase difference between an accelerated and an inertial atoms. For the choice of hydrogen atoms and suitable separation between atoms and mirrors, the required acceleration can be very low.